THE RELATIONSHIP BETWEEN DIVERSIFICATION STRATEGY AND FIRM PERFORMANCE IN DEVELOPED AND EMERGING ECONOMY CONTEXTS: EVIDENCE FROM TURKEY, ITALY AND NETHERLANDS - (:unkn) unknown (VARAZDIN DEVELOPMENT & ENTREPRENEURSHIP AGENCY, 2016)
The aim of this study is to determine whether there is a difference between types of diversification and performance comparing Turkey, Italy and Netherlands. There are studies with the conclusion that the indicators of the relationship between diversification strategies and firm performance of developed countries differ from the indicators of developing countries. The data of 166 firms in Netherlands, 265 firms in Italy and 128 firms in Turkey were analyzed. The data of 2007-2011 was used in the research. Return on Assets (ROA) and Return on Sales (ROS) for financial performance and Entropy Index for diversification were used. According to the results, there is no correlation between total entropy and a performance criterion ROA and ROS in Italy and Netherlands. On the other hand, in Turkey, it is understood that there is a low-level positive correlation between total entropy and firm performance.
Keywords: Diversification Strategy; Entropy Index; Organizational and Financial Performance; BUSINESS GROUPS; ENTROPY MEASURE; CORPORATE; MARKETS; CAPABILITIES; ANTECEDENTS; RESOURCES; INDUSTRY; PATH